PROFIL USAHA INDUSTRI BATU BATA (STUDY KASUS : USAHA BATU BATA ROHIMA DI PEKANBARU) DILIHAT DARI ASPEK PEMASARAN - Rozi Wilandari; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The title of this research are: Brick Industry Business Profile Viewed from the aspect of Marketing (Case Study: brick business Rohima In Pekanbaru). Formulation of the problem: We know that the expected sales target by industrial enterprises brick "Rohima" during the year 2011-2013 was not achieved, with respect to these problems, improvement efforts need to be done, the authors formulate something formulation of the problem, namely how the brick business profile seen from marketing aspects. The purpose of research is to answer the problem formulation above (a) Knowing the brick business profile (Case study: Industrial Bricks Rohima in Pekanbaru) viewed from the aspect of marketing. (B) Knowing the constraints of industrial enterprises bricks (Bricks Case Study Rohima in Pekanbaru) viewed from the aspect of marketing. The benefits of this research are: (a) provide conceptual contribution to the business owners in terms of business management decision making brick industry; (b) for research, develop and increase the practical knowledge in the field of business development; (c) cite this as a material consideration and reference to evaluate as well as the basis for decision making. Conclusions: (1) Industry Rohima existing bricks in Pekanbaru is a small industry, (2) marketing area brick Rohima wide enough to reach the districts in Riau Province, (3) competition in the marketing of bricks in production by industry Rohima bricks in terms of quality and type of product.Keywords : Brick Industry Business Profile Viewed from the aspect of Marketing (Case Study: brick business Rohima In Pekanbaru).